2000
DOI: 10.1007/s002610000018
|View full text |Cite
|
Sign up to set email alerts
|

Gadopentetate dimeglumine as an oral negative gastrointestinal contrast agent for MRCP

Abstract: Diluted intravenous MR contrast agent can be an effective and safe oral negative contrast agent in eliminating signal intensity of the gastrointestinal tract, thus improving the depiction of the biliary system in MRCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 12 publications
1
30
1
4
Order By: Relevance
“…As regards the pharmacological strategy utilizing oral ranitidine, the results of the present study were not similar to those reported by a previous study (5) . No significant difference was observed as regards reduction in signal between scans performed after fasting and after ingestion of 300 mg ranitidine.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…As regards the pharmacological strategy utilizing oral ranitidine, the results of the present study were not similar to those reported by a previous study (5) . No significant difference was observed as regards reduction in signal between scans performed after fasting and after ingestion of 300 mg ranitidine.…”
Section: Discussioncontrasting
confidence: 56%
“…Some authors have put forward opinions which are based on their experience, rather than on hard evidences, indicating that the use oral contrast agent is not necessary (1) . On the other hand, others have demonstrated the usefulness of such a strategy to improve the visualization of the biliopancreatic tree (5,17) . It is important to notice that the latter have not utilized the radial sequence in the 2D breath-hold acquisitions, or have not performed the 3D sequences with RT in the routine evaluation of the biliopancreatic tree in their studies, contrarily to what was done in the present study, and which reduces the undesired superposition of the gastric juice with the biliopancreatic ducts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gadopentetate dimeglumine was chosen due to its safety for oral administration, which has been demonstrated [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…However, because of limited contrast resolution and relative inability to show the anastomotic site, CT correctly identifies the site of biliary obstruction in 10% of patients only [2,16] . The main role for CT is then to assess HAT [19] and/or detect intra-and extra-hepatic hypoattenuating collections when a suspicious biloma has gadolinium chelate contrast agent just before the acquisition of MRC in order to suppress overlapping fluid signal from the stomach and/or duodenum with paramagnetic effects on the T2 relaxation time [23] . However, because of the risk to mask the vaterian region of the common bile duct as a possible site of BC, the use of oral negative contrast agent is a matter of expertise and institutional preferences.…”
Section: Diagnostic Approach To Biliary Complicationsmentioning
confidence: 99%